Mitochondrial matrix pH acidifies during anoxia and is maintained by the F(1)F(o)‐ATPase in anoxia‐tolerant painted turtle cortical neurons - Hawrysh, Peter John (FEBS Open Bio, 2019)
The western painted turtle (Chrysemys picta bellii) can survive extended periods of anoxia via a series of mechanisms that serve to reduce its energetic needs. Central to these mechanisms is the response of mitochondria, which depolarize in response to anoxia in turtle pyramidal neurons due to an influx of K(+). It is currently unknown how mitochondrial matrix pH is affected by this response and we hypothesized that matrix pH acidifies during anoxia due to increased K(+)/H(+) exchanger activity. Inhibition of K(+)/H(+) exchange via quinine led to a collapse of mitochondrial membrane potential (Ψ(m)) during oxygenated conditions in turtle cortical neurons, as indicated by rhodamine‐123 fluorescence, and this occurred twice as quickly during anoxia which indicates an elevation in K(+) conductance. Mitochondrial matrix pH acidified during anoxia, as indicated by SNARF‐1 fluorescence imaged via confocal microscopy, and further acidification occurred during anoxia when the F(1)F(o)‐ATPase was inhibited with oligomycin‐A, indicating that ΔpH collapse is prevented during anoxic conditions. Collectively, these results indicate that the mitochondrial proton electrochemical gradient is actively preserved during anoxia to prevent a collapse of Ψ(m) and ΔpH.